2023
DOI: 10.3390/land12081499
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Agro-Biodiversity through Leverage Factors: Land Use, Farmer Practices and Public Policies

Abstract: Understanding the socio-economic channels through which farmers affect agro-biodiversity (ABD) represents a relevant research area, especially in the light of the new sustainable development paradigm. Supporting ABD is one of the main goals of the EU Green Deal and the agricultural sector is being called on for a higher commitment. Nowadays, ABD interventions are linked not only to the genetic and natural resources of species, but also to farming practices, land management, living standards in rural areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Suppose that it is not possible to identify theoretical recommended values. In that case, the lower and upper thresholds can be defined according to the minimums and maximums (min-max) of a set of agents, such as countries, regions, projects, or farms, among others [7,30,31,35,36]. This method does not consider the discrepancy between the actual value of an indicator and the desired value.…”
Section: Standardization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppose that it is not possible to identify theoretical recommended values. In that case, the lower and upper thresholds can be defined according to the minimums and maximums (min-max) of a set of agents, such as countries, regions, projects, or farms, among others [7,30,31,35,36]. This method does not consider the discrepancy between the actual value of an indicator and the desired value.…”
Section: Standardization Methodsmentioning
confidence: 99%
“…The study performed by Switek, Sawinska, and Głowicka-Wołoszyn [30] identified socio-economic factors, such as gender and age of the farmer, and the size of the farm, which are associated with higher scores in terms of the natural attractiveness of farms. Additionally, the agrobiodiversity index proposed by Henke and Vaquero-Piñeiro [31] can be used to evaluate farmers' involvement in activities that enhance biodiversity and verify if one mechanism, captured by a specific dimension of the index, is more relevant than others.…”
Section: Composite Indicator Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of recommended practices for biodiversity enhancement and corresponding effects (e.g., productivity, pest control, and soil health, among others) focused on six agricultural variables with recognized influence on biodiversity performance. These included the diversity of plants [22], semi-natural habitats [23], conservation agriculture practices, namely soil cover [24] and reduced tillage [25], and the use of synthetic fertilizers and pesticides [26]. Several biodiversity assessment methodologies considered the diversity of plants [25,[27][28][29] and semi-natural habitats [25,[30][31][32] as relevant indicators of biodiversity performance.…”
Section: Methodsmentioning
confidence: 99%